Servirebbe davvero un buon teatro stabile? - Schiller, Friedrich (Kritik. Rivista di letteratura e critica culturale, 2024)
This text is an unpublished translation of a speech given in Mannheim at the public session of the German Palatinate Society on June 26, 1784 by F. Schiller, a member of this society and adviser to the Duke of Weimar.